Relationship between Gestational Age and Examination Results Triple Elimination of Pregnant Women at UPTD Jayakerta Community Health Center - Nurhasanah, Rika; Anggraeni, Fitri Kurnia (Postgraduate, University of Mataram, 2024)
Human Immunodeficiency Virus (HIV), Syphilis, and Hepatitis B are sexually transmitted infections that pregnant women can pass to their babies. To address this, the Ministry of Health of the Republic of Indonesia has implemented the Triple Elimination program based on WHO recommendations. This study aims to evaluate the effectiveness of the Triple Elimination screening compared to gestational age. Using the Chi-Square method, the research involved 47 pregnant women examined in the first, second, and third trimesters. Data was collected from reports of initial screenings in the first trimester, followed by re-examinations in the subsequent trimesters. A questionnaire with six questions was used. Statistical analysis with a p-value of 0.06 indicated a significant correlation between sexual intercourse habits and an increase in syphilis cases in the third trimester. Additionally, habits related to genital cleaning post-intercourse also significantly impacted syphilis rates. The study highlights the need for ongoing education for pregnant women on preventing sexually transmitted infections and the importance of early detection through Triple Elimination screenings.